Fast collision detection based on projection parallel algorithm - Shen Xue-li; Li Tao (2010 2nd International Conference on Future Computer and Communication, 2010)
This paper describes a fast collision detection algorithm based on projection and parallel. We make irregular three-dimensional objects project to be regular two-dimensional objects in two-dimensional plane and carry on collision detection by combining with spatial projection transformation method, This method improved Ming C. Jin algorithm and Lin-Canny algorithm, so that three-dimensional objects can be detected by the orthographic projection accurately. We distributed two-dimensional projection lists in different computer nodes to sort by combining with parallel, filtering, carrying on intersection collision detection, so accelerate the speed of collision detection.